Strategies to improve the implementation of infection control link nurse programmes in acute-care hospitals. (October 2022) - Dekker, M.; Jongerden, I.P.; de Bruijne, M.C.; Jelsma, J.G.M.; Vandenbroucke-Grauls, C.M.J.E.; van Mansfeld, R.
Summary: Background: Infection control practitioners face several challenges when implementing infection control link nurse (ICLN) programmes. Identification of strategies to address these can improve the impact of current ICLN programmes and guide their future implementation. Aim: We aimed to identify implementation strategies for ICLN programmes in acute-care hospitals with the Consolidated Framework for Implementation Research (CFIR)-Expert Recommendations for Implementing Change (ERIC) Implementation Strategy Matching tool. Methods: An expert panel matched 19 implementation and sustainment barriers, identified in our previous studies, to the most fitting CFIR constructs. Subsequently, we applied the CFIR-ERIC Matching Tool and generated a list of implementation strategies to address these barriers. Findings: Barriers were predominantly found within the CFIR domains 'inner setting' (characteristics of the implementing organization) and 'process' (stages of implementation). With the ERIC Matching Tool, we identified the 10 most important strategies to address barriers of implementation of ICLN programmes: identify and prepare champions, conduct local consensus discussions, assess for readiness and identify barriers and facilitators, inform local opinion leaders, use facilitation, create a learning collaborative, conduct local needs assessments, develop a formal implementation blueprint, build a coalition, and identify early adopters. Conclusion: The CFIR domains 'inner setting' and 'process' appeared to be the most important to impede implementation of ICLN programmes in acute-care hospitals. Application of the CFIR-ERIC tool highlighted the identification and preparation of champions as the leading strategy for the successful implementation of these programmes. With this tool, strategies can be specifically tailored towards local implementation and sustainment barriers.